Tanggung Jawab Hukum Pelaku Usaha atas Kerugian Konsumen yang Disebabkan oleh Perangkat Medis yang Tidak Memenuhi Standar - Ratih Pratiwi syurkawi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article addresses business operators' legal liability for consumer losses caused by substandard medical devices and evaluates consumer protection adequacy under Law No. 17 of 2023 on Health and Law No. 8 of 1999 on Consumer Protection. The core problem is the disconnect between risk-based sectoral regulation and general product liability doctrine, weakening protection for high-risk devices. The study uses normative juridical methods with statutory, conceptual and case approaches. Findings reveal an accountability scheme of administrative, civil and criminal sanctions, though strict liability remains limited. The study proposes regulatory harmonization, strict liability and product insurance.